Bupropion for the treatment of apathy in Alzheimer disease a randomized clinical trial - Maier, Franziska; Spottke, Annika; Bach, Jan-Philipp; Bartels, Claudia; Buerger, Katharina; Dodel, Richard; Fellgiebel, Andreas; Fliessbach, Klaus; Frölich, Lutz; Hausner, Lucrezia; Hellmich, Martin; Kloeppel, Stefan; et al. (JAMA network open, 2020)
This randomized clinical trial examines the efficacy and safety of the dopamine and noradrenaline reuptake inhibitor bupropion in the treatment of apathy in patients with dementia of Alzheimer type. Importance Apathy is a frequent neuropsychiatric symptom in dementia of Alzheimer type and negatively affects the disease course and patients' and caregivers' quality of life. Effective treatment options are needed. Objective To examine the efficacy and safety of the dopamine and noradrenaline reuptake inhibitor bupropion in the treatment of apathy in patients with dementia of Alzheimer type. Design, Setting, and Participants This 12-week, multicenter, double-blind, placebo-controlled, randomized clinical trial was conducted in a psychiatric and neurological outpatient setting between July 2010 and July 2014 in Germany. Patients with mild-to-moderate dementia of Alzheimer type and clinically relevant apathy were included. Patients with additional clinically relevant depressed mood were excluded. Data analyses were performed between August 2018 and August 2019. Interventions Patients received either bupropion or placebo (150 mg for 4 weeks plus 300 mg for 8 weeks). In case of intolerability of 300 mg, patients continued to receive 150 mg throughout the study. Main Outcomes and Measures Change on the Apathy Evaluation Scale-Clinician Version (AES-C) (score range, 18-72 points) between baseline and week 12 was the primary outcome parameter. Secondary outcome parameters included measures of neuropsychiatric symptoms, cognition, activities of daily living, and quality of life. Outcome measures were assessed at baseline and at 4, 8, and 12 weeks. Results A total of 108 patients (mean [SD] age, 74.8 [5.9] years; 67 men [62%]) were included in the intention-to-treat analysis, with 54 randomized to receive bupropion and 54 randomized to receive placebo. The baseline AES-C score was comparable between the bupropion group and the placebo group (mean [SD], 52.2 [8.7] vs 50.4 [8.2]). After controlling for the baseline AES-C score, site, and comedication with donepezil or galantamine, the mean change in the AES-C score between the bupropion and placebo groups was not statistically significant (mean change, 2.22; 95% CI, -0.47 to 4.91; P = .11). Results on secondary outcomes showed statistically significant differences between bupropion and placebo in terms of total neuropsychiatric symptoms (mean change, 5.52; 95% CI, 2.00 to 9.04; P = .003) and health-related quality of life (uncorrected for multiple comparisons; mean change, -1.66; 95% CI, -3.01 to -0.31; P = .02) with greater improvement in the placebo group. No statistically significant changes between groups were found for activities of daily living (mean change, -2.92; 95% CI, -5.89 to 0.06; P = .05) and cognition (mean change, -0.27; 95% CI, -3.26 to 2.73; P = .86). The numbers of adverse events (bupropion group, 39 patients [72.2%]; placebo group, 33 patients [61.1%]) and serious adverse events (bupropion group, 5 patients [9.3%]; placebo group, 2 patients [3.7%]) were comparable between groups. Conclusions and Relevance Although it is safe, bupropion was not superior to placebo for the treatment of apathy in patients with dementia of Alzheimer type in the absence of clinically relevant depressed mood. Question Is bupropion an effective and safe treatment for apathy in nondepressed patients with dementia of Alzheimer type? Findings In this 12-week, multicenter, double-blind, placebo-controlled, randomized clinical trial, 54 patients received bupropion and 54 received placebo. The mean change in the Apathy Evaluation Scale-Clinician Version score was not statistically significant between the treatment groups. Meaning Bupropion did not improve apathy in patients with dementia of Alzheimer type without depressed mood.
Gesehen am 02.11.2020